Residents' Perceptions of Bagot Tourism Village Development in Samosir Regency - Marlina Situmorang; Trisna Putra; Pasaribu (Pt. Threeple Herphi Educate, 2026)
This study explores residents' perceptions of Bagot Tourism Village development in Samosir Regency through cognitive, affective, and conative dimensions. Bagot Tourism Village emerged from a community-based initiative and has developed around local palm-sap culinary products, rural scenery, and community-managed visitor activities, but coordination and shared management remain uneven. A descriptive qualitative design was used. Eight informants were selected through purposive and snowball sampling: one Samosir Regency Tourism Office representative, the Bagot Village head, the tourism awareness group leader, and five residents living near the tourism area. Fieldwork was conducted from 26 December 2022 to 15 January 2023 using semi-structured interviews, direct observation, and documentation. Data were reduced, displayed, coded into cognitive, affective, and conative categories, compared across informant groups, and triangulated across data sources. Cognitively, informants recognized the village's tourism potential, but knowledge of tourism-village governance, benefit distribution, and visitor management remained uneven. Affectively, most informants supported tourism development, although land-use and fairness concerns created points of tension. Conatively, residents participated in collective activities, but some actions remained oriented toward individual interests rather than shared programs. These findings represent the perspectives of the eight informants in the Bagot context and are not intended for statistical generalization. The study indicates that a resident forum, transparent benefit-sharing arrangements, clear land-use and participation rules, and continuous practical tourism education should be prioritized.